The role of open software in innovation and standardization in radiology. - Erickson BJ; Langer S; Nagy P (Journal of the American College of Radiology, 2005)
The use of open-source software (OSS), in which developers release the source code to applications they have developed, is popular in the software industry. This is done to allow others to modify and improve software (which may or may not be shared back to the community) and to allow others to learn from the software. Radiology was an early participant in this model, supporting OSS that implemented the ACR-National Electrical Manufacturers Association (now Digital Imaging and Communications in Medicine) standard for medical image communications. In radiology and in other fields, OSS has promoted innovation and the adoption of standards. Popular OSS is of high quality because access to source code allows many people to identify and resolve errors. Open-source software is analogous to the peer-review scientific process: one must be able to see and reproduce results to understand and promote what is shared. The authors emphasize that support for OSS need not threaten vendors; most vendors embrace and benefit from standards. Open-source development does not replace vendors but more clearly defines their roles, typically focusing on areas in which proprietary differentiators benefit customers and on professional services such as implementation planning and service. Continued support for OSS is essential for the success of our field.